Identification Of Cholestrol Level Testing HDL And LDL In Hypertension Patients At Santa Elisabeth Medan Hospital - Cornelius Manik; Putri Hartanti Hulu; Rica Vera Br Tarigan (Jurnal EduHealth, 2022)
Number of people with hypertension continues to increase every year, there will be 1.5 billion people affected by hypertension, and every year 9, 4 million people died due to hypertension and its complications. The supporting examination for hypertension is an examination of the total levels of HDL and LDL cholesterol. This study aims to identify the examination of HDL and LDL cholesterol levels in patients with hypertension at Santa Elisabeth Hospital Medan 2022. This study used a descriptive analytic design. The population was obtained from medical record data, namely all inpatients and outpatients suffering from hypertension at Santa Elisabeth Hospital Medan for the last 3 months from January to March 2022 as many as 278 people with a total sample of 73 using purposive sampling technique. The examination was carried out using an automated chemistry analyzer Siemens dimension EXL 200. The results showed that more hypertensive respondents had abnormal HDL levels as many as 38 respondents (52.1%) and more than 69 respondents (94.5) had normal LDL levels. %). So from these results it was concluded that there was an abnormal increase in HDL levels and a decrease in LDL levels in patients with hypertension